INFLASI DAN TINGKAT KEMISKINAN DI INDONESIA - Novegya Ratih Primandari (STIE DWI SAKTI BATURAJA, 2018)
This study aims to determine the effect of inflation on poverty levels in Indonesia in the period 2001 - 2017. The analytical tool used is simple linear regression. The results of the analysis show that inflation has a positive effect on the poverty level in Indonesia for the period 2001 - 2017. The contribution of the influence of inflation to the rise and fall of poverty is 29.2%. While the remaining 70.8% is influenced by other factors not observed in the study. Among other things, the number of poor people, the quality of human resources, and access to capital.